Becoming more sedentary? Changes in recovery positions of Mallard Anas platyrhynchos ringed in the Camargue, France, over the last 50 years - Guillemain, Matthieu; Champagnon, Jocelyn; Massez, Gregoire; Pernollet, Claire A.; George, Thierry; Momerency, Andre; Simon, Geraldine (Wildfowl, 2015)
Earlier studies from central and northern Europe have found a shortening of the ringÂ recovery distance in Mallard Anas platyrhynchos, which was generally attributed to climateÂ change leading to a northwards shift of the wintering range. Here we show that recoveryÂ distances for Mallard ringed during winter in the Camargue (southern France), at theÂ southern end of their range, have also shortened over the last 50 years, from a mean of 417 km (s.e. Â± 17.4) for birds ringed between 1950â€“1978 to 74 km (Â± 28.9) for birdsÂ ringed between 2002â€“2013. In contrast to the studies in other areas, however, the moreÂ recent recoveries of Mallard ringed in the Camargue were made to the south and west ofÂ where they were previously, and changes in ring recoveries were likely caused by a greaterÂ proportion of sedentary birds among the Camargue wintering population. DiscardingÂ unlikely methodological biases that may explain the pattern observed, we suggest threeÂ non-mutually exclusive hypotheses to explain such a change: a) increased attractiveness ofÂ Camargue habitats as a winter quarter, with migrant birds now staying for longer periodsÂ and allowing more local recoveries, b) hybridization between resident captive-bredÂ and wild Mallards, and c) former migrants from northern Europe now foregoingÂ long migration to this distant winter quarter due to climate change. Future studiesÂ combining genetic and isotope analyses may help in teasing these hypotheses apart, toÂ provide a better understanding of the factors leading to such increased sedentarity.